ANALISIS PENGARUH HEDONIC VALUE, PERSEPSI MANFAAT, DAN PERSEPSI KREDIBILITAS TERHADAP KUALITAS LAYANAN DAN DAMPAKNYA PADA MINAT BELI ULANG DENGAN MEDIASI CUSTOMER VALUE Studi kasus pada Oriflame Produk Lipstik di Kota Semarang - Fajariah, Fathi (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2014)
The purpose of this research is to test the influences of hedonic value, perceived usefulness,and perceived credibility on service quality and customer value to increase rebuying intention.Using these variables, the usage of these variables are able to solve the arising problemwithin PT. Oriflame Semarang.Using the Structural Equation Modeling (SEM). The samples size of this research is 100customers PT. Oriflame Semarang. The results show that the hedonic value, perceivedusefulness, and perceived credibility on service quality and customer value to increase rebuyingintention.The effect of hedonic value on service quality are significant; The effect of perceived usefullnesson service quality are significant; The effect of perceived credibility on service quality aresignificant; The effect service quality on customer value are significant; The effect of hedonicvalue on rebuying intention are significant; The effect of perceived credibility on rebuyingintention are significant; The effect of customer value on rebuying intention are significant;and The effect service quality on rebuying intention are significant.